The Development of Law in Indonesia is Linked to Hans Kelsen's Positivism Theory - Sungguh Raja Sembiring; Heddy Permana Putra; Yuninda Dwi Kartika; Yoga Gustiadi; Dani Durahman (Rechtsvinding, 2026)
The evolution of legal theory from classical to modern periods reveals significant shifts in how law is understood and conceptualized. While earlier legal theories were strongly shaped by philosophical and political thought, modern legal theory is largely developed within frameworks constructed by legal scholars themselves. Legal positivism, particularly Hans Kelsen’s Pure Theory of Law, argues that law must be separated from non-juridical elements such as social, political, historical, and ethical factors. Nevertheless, in the Indonesian context, law cannot be viewed solely through textual norms. Its effectiveness depends on legal culture, law enforcement performance, and supporting infrastructure. This complexity demonstrates the limitations of a purely positivistic approach when applied to a multidimensional legal system. Therefore, the ongoing development of legal philosophy shows that law cannot be confined to statutory texts alone, but must be understood as a living social institution influenced by broader external factors.